Out of the Lab and On the Market : How Sony Computer Science Labs (SonyCSL) Turn Research into Profits /: How Sony Computer Science Labs (SonyCSL) Turn Research into Profits. (2017) - Natsume, Tetsu; Tokoro, Mario
No abstract available